Laser-Induced graphene - Ye, Ruquan; Tour, James M. (Singapore : Jenny Stanford Publishing Pte. Ltd., 2021)
LIG is a revolutionary technique that uses a common CO2 infrared laser scriber, like the one used in any machine shop, for the direct conversion of polymers into porous graphene under ambient conditions. This technique combines the preparation and patterning of 3D graphene in a single step, without the use of wet chemicals. The ease in the structural engineering and excellent mechanical properties of the 3D graphene obtained have made LIG a versatile technique for applications across many fields. This book compiles cutting-edge research on LIG by different research groups all over the world. It discusses the strategies that have been developed to synthesize and engineer graphene, including controlling its properties such as porosity, composition, and surface characteristics. The authors are pioneers in the discovery and development of LIG and the book will appeal to anyone involved in nanotechnology, chemistry, environmental sciences, and device development, especially those with an interest in the synthesis and applications of graphene-based materials.
5. Laser-Induced Graphene for Water Treatment -- 5.1 Laser-Induced Graphene for Separation -- 5.2 Laser-Induced Graphene for Antifouling -- 6. Laser-Induced Graphene Sensors -- 6.1 Chemical Sensors -- 6.2 Gas Sensors -- 6.3 Piezoresistive Sensors -- 6.4 Temperature Sensors -- 7. Specific Laser Cutter Settings -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Graphene; Nanostructured materials -- Mechanical properties; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Magnetism